Emergency Department care of childhood epistaxis. Issue 8 (19th August 2016) - Béquignon, E; Teissier, N; Gauthier, A; Brugel, L; De Kermadec, H; Coste, A; Prulière-Escabasse, V
Abstract : Objective: The aim of this review is to determine an efficient and safe primary strategy care for paediatric epistaxis. Data sources: We searched PubMed and Cochrane databases for studies referenced with key words 'epistaxis AND childhood'. This search yielded 32 research articles about primary care in childhood epistaxis (from 1989 to 2015). Bibliographic references found in these articles were also examined to identify pertinent literature. We compared our results to the specific management of adult epistaxis classically described in the literature. Results: Epistaxis is one of the most common reasons for referral of children to a hospital ENT outpatient department. The bleeding usually originates from the anterior septum, as opposed to adults. Crusting, digital trauma, foreign bodies and nasal colonisation with Staphylococcus aureus have been suggested as specific nosebleed factors in children. Rare aetiologies as juvenile nasopharyngeal angiofibroma appear later during adolescence. There are different modes of management of mild epistaxis, which begin with clearing out blood clots and bidigital compression. An intranasal topical local anaesthetic and decongestant can be used over 6 years of age. In case of active bleeding, chemical cauterisation is preferred to anterior packing and electric cauterisation but is only feasible if the bleeding site is clearly visible. In case of non-active bleeding in children, and in those with recurrent idiopathic epistaxis, antiseptic cream is easy to apply and can avoid 'acrobatic' cauterisation liable to cause further nasal cavity trauma. Conclusions: Aetiologies and treatment vary with patient age and the existence or not of active bleeding at the time of the examination. Local treatments are usually easy to perform, but physicians have to ponder their indications depending on the possible complications in order to inform parents and to know paediatric epistaxis specificities.